Design thinking in project management – assessment of application possibility - Sońta-Drączkowska, Ewa; Bednarska-Wnuk, Izabela (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The article discusses the possibilities of using the design thinking approach in project management. This approach has become popular in recent decades both in practice and in literature in the field of management sciences. In particular, in the context of innovation management, engaging the user or customer in the product development process and creative approaches to solving complex problems. Several studies have emerged regarding the possibilities and advantages of the application of design thinking in project management. This has been especially discussed in the context of exploratory projects. Nevertheless, there is still a research gap regarding how design thinking practices can be integrated into project-based activities of an enterprise. Based on a comprehensive literature review and analysis of the design thinking approach proposed by Hasso Plattner Institute, the author analyzes the advantages and limitations for the application of the method in projects and also proposes areas for future research.